Artificial intelligence-related technologies for municipal solid waste management: A review and new insights from smart cities - Tachin Chin; Ying Fan; Chien-Liang Lin; Yu-Cheng Lin; Kuo-Ti Liao (Sustainable Cities and Society, 2026)

First visualization of intact sperm storage tubules in the duck oviduct: A fluorescent labeling approach for targeted SST sampling - Hsiu-Lien Herbie Lin; Chin-Hui Su; Shih-Yi Huang; Ya-Hsin Kuo; Liang-Yuan Wei; Yi-Ying Chang; Ching-Wei Chang; Jeng-Fang Huang; Pascal Mermillod; Chih-Hsiang Cheng (Animal Reproduction Science, 2026)

Mobilized-clay-driven toppling: A new mechanism resolving the “energy paradox” of under-dip slope failure in flysch terrains - Thanh-Tùng Nguyễn; Ivo Baroň; Filip Hartvich; Jiří Havlík; Lenka Kociánová; Jan Klimeš; Jan Černý; Martin Šutjak; Václav Dušek; Cheng-Han Lin; Chia-Han Tseng; Yi-Chin Chen; et al. (Landslides, 2026)

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Beehive-entrance imaging and deep learning for real-time monitoring of Varroa destructor in apiculture - Tai-Sheng Su; Chin-Chun Wu; Tzu-Yin Lin; Cheng-Hsiang Liu (Journal of Invertebrate Pathology, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Association between urinary metabolites of 1,3-butadiene and toluene exposure with kidney function indices in Taiwanese school-aged children living near a petrochemical complex - Po-Keng Cheng; Vinoth Kumar Ponnusamy; Wei-Hong Lin; Jeganathan Chinnadurai; Pei-Chien Tsai; Cai-Yu Chen; Wan-Ting Chang; Po-Chin Huang (Environmental Pollution, 2026)

Microbial, genetic, and urban drivers of ant invasions - Wei-Jiun Lin; Po-Wei Hsu; Edward L Vargo; Chin-Cheng Scotty Yang (Current Opinion in Insect Science, 2025)

An in vivo NanoBiT-based pseudoviral biosensor for real-time monitoring of SARS-CoV-2 spike/hACE2 interactions and therapeutic screening - Cheng-Han Lin; Meng-Wei Lin; Xin-Rui Yang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chin-Hung Tsai; Chih-Sheng Lin (Analytica Chimica Acta, 2025)

Functional oligosaccharides derived from the degradation of natural Dendrobium polysaccharides by human gut microbes regulate physiological factors associated with type-2 diabetes - Ming-Che Cheng; Hsi-Mei Chen; Bao-Jiun Bai; Tsu-Yuan Chang; Meng-Chin Chen; Yen- Ting Lin; Chi-Kung Ni; Mei-Kuang Lu; Hui-Kang Liu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Adaptation and carbon reduction for petroleum contaminated soil remediation in response to climate change-a case study of phytoremediation combined with biochar - Pei-Cheng Cheng; Min-Siou Lin; Chin-Yuan Huang; Shu-Fen Cheng; Yuan-Chung Lin (Journal of Environmental Management, 2025)

Navigating crowds: Reconsidering visitor recreational experience and crowding preference for a forest park in Taiwan - Wan-Yu Liu; Chin-Chun Yen; Rachel S.K. Lee; Chun-Cheng Lin (Forest Policy and Economics, 2025)

Five novel RNA viruses of the invasive big-headed ant (Pheidole megacephala) - Charly T. Hartle; Chih-Chi Lee; Hung-Wei Hsu; Chun-Yi Lin; Kuan-Ling Liu; Joey Yin-Xin Chang; John A. Lawrence; Jia-Wei Tay; Chin-Cheng Scotty Yang (Archives of Virology, 2025)
The African big-headed ant, Pheidole megacephala , is one of the most destructive invasive ant species, posing a significant threat to native biodiversity and ecosystem function, particularly in island ecosystems. Despite recent efforts to characterize pathogens in other major invasive ants, P . megacephala has received comparatively little attention. In this study, we characterized five novel RNA viruses actively replicating in P . megacephala , which we have named Pheidole megacephala virus 1–5 (PmV1-5), and examined viral diversity and prevalence in two invasive populations in Taiwan and Hawaii. This ant possesses a unique trait of true morphological worker dimorphism (major and minor), allowing us to test whether virus prevalence differs between the major and minor worker castes. Our findings indicate that all five novel viruses were present in both populations, but viral prevalence was higher in Hawaii than in Taiwan, potentially due to differences in supercolony structure. Multiple-virus infections were common, with coinfection by PmV1 and PmV5 being the most frequent. Notably, we found no significant difference in infection patterns between major and minor workers, suggesting that virus distribution is stable within colonies and that sampling different castes does not introduce bias in pathogen detection. This study represents the first characterization of viral pathogens in P . megacephala and may contribute to the development of microbial control strategies against this globally invasive ant.

Fire ants exhibit self-medication but lack preventive behavioral immunity against a viral pathogen - Fang-Ling Chloe Liu; Wei-Jiun Lin; Liam McMillan; Chin-Cheng Scotty Yang (Journal of Invertebrate Pathology, 2025)

Building with nature: Morphological spatial pattern of green infrastructure in urban heat mitigation - Bau-Show Lin; Yu-Hua Tsai; Han-Chin Chang; Chin-Chung Yu; Cheng-I Hsieh (Building and Environment, 2025)

Spatial patterns of essential fish habitats in the western Taiwan coast - Yu-Jia Lin; Chien-Cheng Lai; Hsu-Sen Chen; Tsu-Chun Chen; Kuo-Shu Chen; Norhafiz Hanafi; Pei-Jie Meng; Ying-Chin Fang; Chiee-Young Chen; Hsin-Ming Yen; Meng-Hsien Chen (Estuarine, Coastal and Shelf Science, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Genetic Analysis of Polyunsaturated Fatty Acids Biosynthesis Pathway Determines Four Distinct Thraustochytrid Types - Sou‐Yu Cheng; Yi‐Jing Chen; Hsiu‐Chin Lin; Hsin‐Yang Chang; Ming‐Der Huang (Environmental Microbiology, 2025)
Thraustochytrids, diverse marine unicellular protists encompassing over 10 recognised genera, are renowned for synthesising polyunsaturated fatty acids (PUFAs), with content and composition varying substantially across genera. While PUFAs are known to be produced via PUFA synthase (PUFA‐S) and/or elongase/desaturase (ELO/DES) pathways, the distinctions in genes involved remain unexplored. This study analysed PUFA biosynthetic genes in 19 thraustochytrid strains across six genera, categorising them into four types. Type I exclusively utilises the ELO/DES pathway, Type II employs both PUFA‐S and complete ELO/DES pathways, while Types III and IV primarily rely on PUFA‐S, with Type III lacking the canonical Δ9 desaturase and Type IV missing most desaturase and elongase enzymes. Notably, the Δ9 desaturase and ATP‐citrate lyase ( ACLY ) are exclusive to Types I and II, while β‐carotene hydroxylase ( CrtZ ) is absent in these types. ACLY absence suggests alternative acetyl‐CoA supply pathways in Types III and IV, whereas CrtZ absence implies either a lack of specific xanthophylls or alternative biosynthetic pathways in Types I and II. Synteny analysis revealed conserved genomic organisation of PUFA biosynthetic genes, indicating a shared evolutionary trajectory. This study provides insights into the genetic diversity underlying PUFA biosynthesis in thraustochytrids, while proposing putative evolutionary pathways for the four lineages.

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Unraveling the heterogeneous hydrogeological characteristics in the Choushui River alluvial fan, Taiwan, through observations from the multi-layer compaction monitoring wells - Reyhan Azeriansyah; Kuo-En Ching; Cheng-Wei Lin; Kuo-Chin Hsu; Pei-Ching Tsai; Chao-Lung Yeh; Ruey-Juin Rau (Engineering Geology, 2025)

Application of seismically derived tilt signals to characterize groundwater flow regimes: An example from a constant-rate pumping test in Taiwan - Chu-Fang Yang; Wu-Cheng Chi; Chien-Chung Ke; Chin-Jen Lin (Journal of Hydrology, 2024)

Seismic rehabilitation of RC frames with innovative precast U-shaped UHPC jackets: Experimental evaluation and computational simulation - Chung-Chan Hung; Chin-Cheng Lin; Tuong Dat Dinh Do (Engineering Structures, 2024)

Advances in perfluoro-alkylated compounds (PFAS) detection in seafood and marine environments: A comprehensive review on analytical techniques and global regulations - Prasath Ramasamy Chandrasekaran; Jeganathan Chinnadurai; Yee Cheng Lim; Chiu-Wen Chen; Pei-Chien Tsai; Po-Chin Huang; Mohsen Gavahian; Gangadhar Andaluri; Cheng-Di Dong; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Environmental Geochemistry and Health, 2024)

Combination of an enzyme-linked immunosorbent assay and an indirect fluorescence assay for a nationwide sero-survey of Toxoplasma gondii infection in pig herds in Taiwan - Kendy Tzu-Yun Teng; Chao-Chin Chang; Shao-Wen Hung; Ming-Tang Chiou; Chao-Nan Lin; Cheng-Yao Yang (Preventive Veterinary Medicine, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Blending Saccharum bagasse and waste cooking oil for biofuel production via microwave co-torrefaction process - Yi-Li Lin; Nai-Yun Zheng; Hsin-Jou Cheng; Chao-Chin Chang (Fuel, 2024)

In vitro and in vivo protective potential of quercetin-3-glucuronide against lipopolysaccharide-induced pulmonary injury through dual activation of nuclear factor-erythroid 2 related factor 2 and autophagy - Pei-Rong Yu; Chiao-Yun Tseng; Cheng-Chin Hsu; Jing-Hsien Chen; Hui-Hsuan Lin (Archives of Toxicology, 2024)

Meteotsunamis in the Tamsui River estuary, Taiwan - Li-Ching Lin; Wen-Cheng Liu; Chin H. Wu (Estuarine, Coastal and Shelf Science, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

A 16-year meteotsunami climatology in the coastal areas of southern Asia-Pacific Ocean - Li-Ching Lin; Wen-Cheng Liu; Chin H. Wu (Frontiers in Marine Science, 2024)
This study presents the meteotsunami behavior in response to different storm types in the coasts of southern Asia-Pacific Ocean from 16 years water level records. Through the size- frequency analysis, the dangerous meteotsunami, wave height exceeding 0.3 m, can occur up to 44 events per year. Notably, during the extreme waves of the 2007 event, wave heights reached approximately 0.9-1.5 m in the Taiwan Strait and the western coastal areas of Taiwan. We have classified storms into six types by radar reflectivity images and satellite-derived precipitation. Findings indicate that predicted wave heights caused by bows and typhoons could reach hazardous magnitude of exceeding 2 m in a 100-yr interval. Spatial and temporal analysis reveals that meteotsunami occurrences are most frequent in the western regions during the winter to early spring months (December to April). Of all meteotsunami occurrences, cluster storms are identified as the most prevalent atmospheric forcing, accounting for 60% of meteostunamis. Typhoons have a 20% association with meteotsunamis along the east coasts of Taiwan during late summer to autumn. On the east coasts, typhoon type-induced events may be attributed to the combination effect of meteotsunamis and infra-gravity waves. Overall, this study provides the first comprehensive examination of meteotsunami-storm characteristics and their associated hazard risks in the coastal areas of the southern Asia-Pacific Ocean.

Transient ground bulge derived from a dense broadband seismic array during an aquifer step-drawdown pumping test - Wu-Cheng Chi; Chu-Fang Yang; Sebastian Wege; Chin-Jen Lin; Chien-Chung Ke (Journal of Hydrology, 2024)

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

Epitomizing biohydrogen production from microbes: Critical challenges vs opportunities - Jia Min Woon; Kuan Shiong Khoo; Asla A. AL-Zahrani; Meznah M. Alanazi; Jun Wei Lim; Chin Kui Cheng; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sun Yi-Ming; Kuen-Song Lin; John Chi-Wei Lan; Md Sohrab Hossain; et al. (Environmental Research, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

The effect of isovitexin on lipopolysaccharide-induced renal injury and inflammation by induction of protective autophagy - Chiao-Yun Tseng; Pei-Rong Yu; Cheng-Chin Hsu; Hui-Hsuan Lin; Jing-Hsien Chen (Food and Chemical Toxicology, 2023)

Attentional focus effect on dual-task walking in Parkinson’s disease with and without freezing of gait - Yu-An Chen; Ruey-Meei Wu; Chen-Hsing Sheu; Chin-Hsien Lin; Cheng-Ya Huang (GeroScience, 2023)

Using cluster algorithms with a machine learning technique and PMF models to quantify local-specific origins of PM2.5 and associated metals in Taiwan - Chin-Yu Hsu; Jhy-Charm Soo; Sheng-Lun Lin; Chih-Da Wu; Kai Hsien Chi; Wen-Chang Hsu; Chun-Chieh Tseng; Yu-Cheng Chen (Environmental Pollution, 2023)

Equilibrative Nucleoside Transporter 1 is a Target to Modulate Neuroinflammation and Improve Functional Recovery in Mice with Spinal Cord Injury - Kuan-Yu Chen; Chiao-Shin Lu; Cheng-Yoong Pang; Chin-Jui Ho; Kuo-Chen Wu; Hsiu-Wei Yang; Hsin-Lin Lai; Yijuang Chern; Chun-Jung Lin (Molecular Neurobiology, 2023)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Applying Artificial Intelligence (AI) Techniques to Implement a Practical Smart Cage Aquaculture Management System - Chung-Cheng Chang; Jung-Hua Wang; Jenq-Lang Wu; Yi-Zeng Hsieh; Tzong-Dar Wu; Shyi-Chy Cheng; Chin-Chun Chang; Jih-Gau Juang; Chyng-Hwa Liou; Te-Hua Hsu; Yii-Shing Huang; Cheng-Ting Huang; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose This paper presents our team’s results to establish an AIoT smart cage culture management system. Methods According to the built system, the farmed field information is transmitted to the data platform of Ocean Cloud, and all collected data and analysis results can be applied to the cage culture field after the bigdata analysis. Results This management system successfully integrates AI and IoT technologies and is applied in cage culture. Using underwater biological analysis images and AI feeding as examples, this paper explains how the system integrates AI and IoT into a feasible framework that can constantly acquire information about the health status of fish, survival rate of fish, as well as the feed residuals. Conclusion The results of our research enable the aquaculture operators or owners to efficiently reduce the feed residual, monitor the growth of fish, and increase fish survival rate, thereby increasing the feed conversion rate.

Dynamic Anthropometrics of Preschool Children in Taiwan for Playground Equipment Designs - I-Fang Cheng; Chien-Ju Lin; Li-Chieh Kuo; Bih-Jen Hsue; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Differential time-lag effects of ambient PM2.5 and PM2.5-bound PAHs on asthma emergency department visits - Shih-Chang Hsu; Jer-Hwa Chang; Chon-Lin Lee; Wen-Cheng Huang; Yuan-Pin Hsu; Chung-Te Liu; Shio-Shin Jean; Shau-Ku Huang; Chin-Wang Hsu (Environmental Science and Pollution Research, 2020)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

Correction to: Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Rab18 Collaborates with Rab7 to Modulate Lysosomal and Autophagy Activities in the Nervous System: an Overlapping Mechanism for Warburg Micro Syndrome and Charcot-Marie-Tooth Neuropathy Type 2B - Fang-Shin Nian; Lei-Li Li; Chih-Ya Cheng; Pei-Chun Wu; You-Tai Lin; Cheng-Yung Tang; Bo-Shiun Ren; Chin-Yin Tai; Ming-Ji Fann; Lung-Sen Kao; Chen-Jee Hong; Jin-Wu Tsai (Molecular Neurobiology, 2019)

Anthropometric Database of the Preschool Children from 2 to 6 Years in Taiwan - I-Fang Cheng; Li-Chieh Kuo; Chien-Ju Lin; Hsiao-Feng Chieh; Fong-Chin Su (Journal of Medical and Biological Engineering, 2019)

Blood and seminal plasma mercury levels and predatory fish intake in relation to low semen quality - Chin-En Ai; Ching-Jen Li; Ming-Chien Tsou; Jun-Lin Chen; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Science and Pollution Research, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

A prospective study of mitochondrial DNA copy number and the risk of prostate cancer - Amy Moore; Qing Lan; Jonathan N. Hofmann; Chin-San Liu; Wen-Ling Cheng; Ta-Tsung Lin; Sonja I. Berndt (Cancer Causes & Control, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

One-step reverse transcription loop-mediated isothermal amplification for the detection of Capsicum chlorosis virus in Phalaenopsis orchids - Cheng-Ping Kuan; Yu-Fei Lin; Yu-Chun Lin; Chin-Chih Chen (Journal of General Plant Pathology, 2016)

Maternal exposure to di-(2-ethylhexyl) phthalate exposure deregulates blood pressure, adiposity, cholesterol metabolism and social interaction in mouse offspring - Kuan-I Lee; Chin-Wei Chiang; Hui-Ching Lin; Jin-Feng Zhao; Cheng-Ta Li; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Calreticulin Regulates VEGF-A in Neuroblastoma Cells - Wen-Chin Weng; Kuan-Hung Lin; Pei-Yi Wu; Yi-Chien Lu; Yi-Cheng Weng; Bo-Jeng Wang; Yung-Feng Liao; Wen-Ming Hsu; Wang-Tso Lee; Hsinyu Lee (Molecular Neurobiology, 2015)

Exploring the benefits of growing bioenergy crops to activate lead-contaminated agricultural land: a case study on sweet potatoes - Shu-Fen Cheng; Chin-Yuan Huang; Kuo-Lin Chen; Sheng-Chien Lin; Yung-Cheng Lin (Environmental Monitoring and Assessment, 2015)

GIS and SBF for estimating groundwater recharge of a mountainous basin in the Wu River watershed, Taiwan - HSIN-FU YEH; HUNG-I LIN; SHING-TSZ LEE; MIN-HSIANG CHANG; KUO-CHIN HSU; CHENG-HAW LEE (Journal of Earth System Science, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

Effect of air-drying and oven-drying treatment on Cr(VI) content and Cr bond forms in soil - Shu-Fen Cheng; Chi-Ying Lai; Sheng-Jie Lin; Chin-Yuan Huang (Environmental Monitoring and Assessment, 2014)

Preventive Effects of Ellagic Acid Against Doxorubicin-Induced Cardio-Toxicity in Mice - Ming-cheng Lin; Mei-chin Yin (Cardiovascular Toxicology, 2013)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

Tetramethylpyrazine decreases hypothalamic glutamate, hydroxyl radicals and prostaglandin-E2 and has antipyretic effects - Chin-Hong Chang; Wu-Tein Huang; Cheng-Hsing Kao; Sheng-Hsien Chen; Cheng-Hsien Lin (Inflammation Research, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Interplay of RsbM and RsbK controls the σ B activity of Bacillus cereus - Lei‐Chin Chen; Jung‐Chi Chen; Jwu‐Ching Shu; Chien‐Yen Chen; Ssu‐Ching Chen; Shu‐Hwa Chen; Chun‐Yen Lin; Chi‐Yu Lu; Chien‐Cheng Chen (Environmental Microbiology, 2012)
Summary The alternative transcription factor σ B of Bacillus cereus controls the expression of a number of genes that respond to environmental stress. Four proteins encoded in the sigB gene cluster, including RsbV, RsbW, RsbY (RsbU) and RsbK, are known to be essential in the σ B ‐mediated stress response. In the context of stress, the hybrid sensor kinase RsbK is thought to phosphorylate the response regulator RsbY, a PP2C serine phosphatase, leading to the dephosphorylation of the phosphorylated RsbV. The unphosphorylated RsbV then sequesters the σ B antagonist, RsbW, ultimately liberating σ B . The gene arrangement reveals an open reading frame, bc1007 , flanked immediately downstream by rsbK within the sigB gene cluster. However, little is known about the function of bc1007 . In this study, the deletion of bc1007 resulted in high constitutive σ B expression independent of environmental stimuli, indicating that bc1007 plays a role in σ B regulation. A bacterial two‐hybrid analysis demonstrated that BC1007 interacts directly with RsbK, and autoradiographic studies revealed a specific C 14 ‐methyl transfer from the radiolabelled S‐adenosylmethionine to RsbK when RsbK was incubated with purified BC1007. Our data suggest that BC1007 (RsbM) negatively regulates σ B activity by methylating RsbK. Additionally, mutagenic substitution was employed to modify 12 predicted methylation residues in RsbK. Certain RsbK mutants were able to rescue σ B activation in a rsbK ‐deleted bacterial strain, but RsbK E439A failed to activate σ B , and RsbK E446A only moderately induced σ B . These results suggest that Glu439 is the preferred methylation site and that Glu446 is potentially a minor methylation site. Gene arrays of the rsbK orthologues and the neighbouring rsbM orthologues are found in a wide range of bacteria. The regulation of sigma factors through metylation of RsbK‐like sensor kinases appears to be widespread in the microbial world.

Assessment of Radar Waveform Retracked Jason-2 Altimetry Sea Surface Heights Near Taiwan Coastal Ocean - Chung-Yen Kuo; Huan-Chin Kao; Hyongki Lee; Kai-Chien Cheng; Li-Ching Lin (Marine Geodesy, 2012)

Classification of non-vegetated areas using Formosat-2 high spatiotemporal imagery: the case of Tseng-Wen Reservoir catchment area (Taiwan) - Cheng-Chien Liu; Chjeng-Lun Shieh; Jia-Chin Lin; An-Ming Wu (International Journal of Remote Sensing, 2011)

Celecoxib induces heme oxygenase-1 expression in macrophages and vascular smooth muscle cells via ROS-dependent signaling pathway - Jang-Shiun Wang; Feng-Ming Ho; Hao-Cheng Kang; Wan-Wan Lin; Kuo-Chin Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Erratum to: Super-ensemble of three RCMs for climate projection over East Asia and Taiwan - Chung-Ming Liu; Ming-Chin Wu; Sahana Paul; Ying-Chen Chen; Shu-Hua Lin; Wei-Shiang Lin; Yen-Chih Lee; Huang-Hsung Hsu; Ren-Yow Tzeng; Cheng-Ta Chen (Theoretical and Applied Climatology, 2011)

Super-ensemble of three RCMs for climate projection over East Asia and Taiwan - Chung-Ming Liu; Ming-Chin Wu; Sahana Paul; Ying-Chen Chen; Shu-Hua Lin; Wei-Shiang Lin; Yen-Chih Lee; Huang-Hsung Hsu; Ren-Yow Tseng; Cheng-Ta Chen (Theoretical and Applied Climatology, 2011)

Anti-herpes simplex virus effects of berberine from Coptidis rhizoma, a major component of a Chinese herbal medicine, Ching-Wei-San - Lengsu William Chin; Yu-Wen Cheng; Shih-Shen Lin; Ya-Yun Lai; Long-Yau Lin; Ming-Yung Chou; Ming-Chih Chou; Chi-Chiang Yang (Archives of Virology, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

A chaos-based visual encryption mechanism for clinical EEG signals - Chin-Feng Lin; Cheng-Hsing Chung; Jia-Hui Lin (Medical & Biological Engineering & Computing, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Expression of a Bacillus thuringiensis toxin (cry1Ab) gene in cabbage (Brassica oleracea L. var. capitata L.) chloroplasts confers high insecticidal efficacy against Plutella xylostella - Cheng-Wei Liu; Chin-Chung Lin; Jinn-Chin Yiu; Jeremy J. W. Chen; Menq-Jiau Tseng (Theoretical and Applied Genetics, 2008)

Expression of a Bacillus thuringiensis toxin (cry1Ab) gene in cabbage (Brassica oleracea L. var. capitata L.) chloroplasts confers high insecticidal efficacy against Plutella xylostella - Cheng-Wei Liu; Chin-Chung Lin; Jinn-Chin Yiu; Jeremy J. W. Chen; Menq-Jiau Tseng (Theoretical and Applied Genetics, 2008)

Complete sequence of a subgroup 3.4 strain of classical swine fever virus from Taiwan - Yu-Ju Lin; Maw-Sheng Chien; Ming-Chung Deng; Chin-Cheng Huang (Virus Genes, 2007)

Stable chloroplast transformation in cabbage (Brassica oleracea L. var. capitata L.) by particle bombardment - Cheng-Wei Liu; Chin-Chung Lin; Jeremy J. W. Chen; Menq-Jiau Tseng (Plant Cell Reports, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Cloning and Characterization of the First Cnidarian ADP-Ribosylation Factor, and Its Involvement in the Aiptasia-Symbiodinum Endosymbiosis - Ming-Chyuan Chen; Ying-Min Cheng; Li-Hsueh Wang; Chorng-Horng Lin; Xing-Yan Huang; Ming-Chin Liu; Ping-Jyun Sung; Lee-Shing Fang (Marine Biotechnology, 2004)

The Heterogeneity in Risk Factors of Lung Cancer and the Difference of Histologic Distribution between Genders in Taiwan - Chien-Hung Lee; Ying-Chin Ko; Li Shu-Chuan Cheng; Ying-Chao Lin; Hsiang-Ju Lin; Ming-Shyan Huang; Jhi-Juh Huang; Eing-Long Kao; Hwei-Zu Wang (Cancer Causes & Control, 2001)

A simple method to determine urea concentration using intact Helicobacter pylori and BromoCresol Purple as a pH indicator - Yuh-Ling Lin; Chien-Tsu Chen; Su-Cheng Lin; Cheng Lee; Hsien-Shou Kuo; Chun-Mean Shih; Yuan-Hsun Hsu; Yi-Ping Chin; Err-Cheng Chan (Biotechnology Letters, 2000)